The Effect of the Congklak Game Method on Class 3 MIN 3 Central Aceh Students' Capability to Count - Siti Pajriati; Samsul Bahri; Misrina Misrina (PGMI IAIN Lhokseumawe, 2023)
Students' ability to count for first-grade students is still lacking. Students should be able to recognize numbers and count at least to reach the number 20 and the same condition is also experienced by grade one students at MIN 3 Aceh Tenggara. The aim of the study was to determine the effect of the congklak game method on the numeracy skills of Class 1MIN 3 Aceh Tenggara. The type of research used by researchers is quantitative with an experimental approach. Based on the data that has been analyzed, there is a significant difference between the experimental class and the control class and it can be seen from the average value of the experimental class pretest obtained 35.87 and the control class obtained 39.78, then there an increase in the posttest average value for the experimental class after the implementation congklak media, but combined with number card media which is equal to 73.91 and for the control class it is equal to 47.17. Testing the hypothesis using the Independent Sample T-Test test so that the post-test scores obtained significant results of 0.000 <0.05 and t count > t table = 6.089 > 2.015, then H0 is rejected and H1 is accepted which can be concluded that there is an influence of the congklak game method on students' numeracy skills in Class 1MIN 3 Southeast Aceh.